Frequency and antibiotic resistance pattern of Salmonella spp. isolated from traditional dairies and raw milks collected in Yazd province, Iran - Raziyeh Barzegar-Bafrouei; Bahador Hajimohammadi; Hengameh Zandi; Gilda Eslami; Hossein Fallahzadeh (Iranian Journal of Microbiology)
Background and Objectives: Salmonellosis is among the most common food-born infections, caused by Salmonella spp. bacteria. Present study has investigated the frequency and antibiotic resistance pattern of Salmonella spp. isolated from traditional dairy products and raw milk supplied in Yazd, Iran. Materials and Methods: In a cross-sectional study, 350 samples of raw milk and traditional dairy products were randomly collected from July to September 2018. Following culturing the samples, isolates went through biochemical tests for phenotypic identification. Results were confirmed through PCR technique by targeting invA gene. Antimicrobial susceptibility test was conducted by means of disk diffusion method. Results: The rate of contamination with Salmonella bacteria was 6.57% in all samples. The PCR assay of all isolates showed that 23 isolates (100%) carried the invA gene. No significant association between the frequency of salmonella spp. and types of dairy and their origin was reported (P>0.05). The highest antibiotic resistance rate among the isolates belonged to tetracycline (34.8%) and the highest sensitivity was seen to imipenem, cefepime, and cefotaxime (each 91.3%). Conclusion: According to our results there has been a rise in multiple drug resistance and contamination rate in traditional dairy products in Yazd province.